Integration of Inter-Religious Communication at Wedding Celebrations In Parda Suka Village, Kaur Regency - Asmarita, Asmarita (UIN Fatmawati Sukarno Bengkulu, 2024)
Tolerance and harmony between religious communities is an important aspect in the life of a pluralistic Indonesian society. Indonesia as a country with diverse ethnicities, religions, languages and cultures requires harmonious cooperation and communication between religious communities to achieve peace and social harmony. In this context, research was conducted with the aim of analyzing the integration of inter-religious communication in realizing religious harmony, with a case study of wedding celebrations in Parda Suka Village, Kaur Regency. The research method used in this research is a type of qualitative research which is described descriptively using an ethnographic approach. The research results show that harmonious inter-religious communication allows religious people with different religious backgrounds to actively participate in wedding celebrations in accordance with their religious teachings. These findings emphasize the importance of promoting positive, open and inclusive communication as a means of maintaining harmony in a heterogeneous society, leading to peace and harmony in everyday life.